Faktor-Faktor Yang Mempengaruhi Pengungkapan Sukarela Modal Intelektual - Istanti, Sri Layla Wahyu (potensio, 2008)
The objective of this study was to analyze the influence ofownership concentration, leverage, board of independence, age offirm and size of firm on Intelectual capital Disclosure (ICD). Theanalysis used independent variable of ownership concentration,leverage, board independence, age of firm and size of firm. And thedependen variables is Intelectual capital Disclosure (ICD) index.Keywords: Intelectual capital Disclosure (ICD); ownershipconcentration; leverage; board of independence; age of firm; size offirm